Educating adolescents : challenges and strategies - Pajares, Frank; Urdan, Timothy C. (Adolescence and education., 2004)
This volume of Adolescence and Education is devoted to an exploration of the challenges facing adolescents and their teachers as well as some of the strategies that have been adopted to address these challenges. Although it is true that most adolescents survive this period of development with few enduring academic or psychological problems, it is also true that a substantial proportion experience depression, bullying and violence in school, sexual harassment, and a widening gap between their personal and academic needs. Many of these problems emerge for the first time during adolescence.